2014
DOI: 10.1002/jclp.22116
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance, Disability, and Posttraumatic Stress Disorder in Utility Workers

Abstract: Sleep disturbance is associated with occupational, social functioning, and PTSD severity, suggesting that ameliorating sleep may lead to increased occupational and social functioning, as well as better treatment responses in PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…PTSD-diagnosed individuals frequently self-report sleep disruption (see, e.g., Giosan et al, 2015 ; Werner et al, 2016 ). However, among studies using objective measures (e.g., polysomnography), there are relatively few, and inconsistent, reports of PTSD-related sleep disruption (see, e.g., Engdahl et al, 2000 ; Calhoun et al, 2007 ; Yetkin et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTSD-diagnosed individuals frequently self-report sleep disruption (see, e.g., Giosan et al, 2015 ; Werner et al, 2016 ). However, among studies using objective measures (e.g., polysomnography), there are relatively few, and inconsistent, reports of PTSD-related sleep disruption (see, e.g., Engdahl et al, 2000 ; Calhoun et al, 2007 ; Yetkin et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the contemporary conception of PTSD was introduced to the psychiatric nomenclature a little more than three decades ago, numerous empirical studies have documented the presence of subjective sleep difficulties in individuals who meet formal diagnostic criteria (Kinzie et al, 1984 ; Mellman et al, 1995a ; Giosan et al, 2015 ; Werner et al, 2016 ). For instance, Giosan et al ( 2015 ) interviewed more than 2,000 men ~29 months after their deployment to the World Trade Center in the days following the 9/11 attacks. They found that those diagnosed with PTSD as a consequence of their deployment experiences reported, relative to those without PTSD, more insomnia and nightmares, more instances of waking feeling unrefreshed, as well as more difficulties with sleep maintenance and snoring.…”
Section: Introductionmentioning
confidence: 99%
“…1 Sleep disturbances exponentially increase distress and dysfunction for these patients. 2 Patients with PTSD and self-reported sleep disturbances are more likely to report functional disability than those without sleep disturbances 2 and comorbid sleep problems may exacerbate existing PTSD symptoms and complicate recovery. 3 …”
Section: Prevalence and Impact Of Self-reported Sleep Disturbances Inmentioning
confidence: 99%
“…Associations between circadian preferences, sleep quality, dissociation, post-traumatic cognitions, and post-traumatic stress disorder (PTSD) among incarcerated offenders (Germain, Buysse, Shear, Fayyad, & Austin, 2004;Germain, Hall, Krakow, Katherine Shear, & Buysse, 2005;Krakow et al, 2004;Krakow et al, 2001;Krakow et al, 2006;Williams, Collen, Orr, Holley, & Lettieri, 2015). Sleep disturbances contribute to manifestation of a more complicated clinical expression of symptoms in PTSD, such as comorbid depression (Krakow et al, 2000), psychiatric distress (Krakow et al, 2007), heightened suicidality and self-injurious behavior (Betts, Williams, Najman, & Alati, 2013;Malik et al, 2014;Pigeon, Pinquart, & Conner, 2012;Short, Ennis, et al, 2015), greater anxiety sensitivity (Babson, Boden, Woodward, Alvarez, & Bonn-Miller, 2013), increased alcohol and drug use (Nishith, Resick, & Mueser, 2001;Saladin, Brady, Dansky, & Kilpatrick, 1995;Short, Babson, Boden, & Bonn-Miller, 2015), and decreased quality of life and functioning (Clum, Nishith, & Resick, 2001;Giosan et al, 2015;Krakow, Melendrez, Johnston, et al, 2002;Short, Allan, & Schmidt, 2017). Poor sleep can significantly contribute to next day affective deterioration, such as increased PTSD symptoms and negative affect (Short et al, 2017;Short et al, 2016).…”
Section: Original Articlementioning
confidence: 99%